Physical activity shifts gut microbiota structure in aged subjects with overweight/obesity and metabolic syndrome - Ruiz-Limón, Patricia; Muralidharan, Jananee; Gomez-Perez, Ana M.; Murri, Mora; Vioque, Jesús; Corella, Dolores; Fitó, Montse; Vidal, Josep; Salas-Salvadó, Jordi; Torres-Collado, Laura; Coltell, Oscar; Atzeni, Alessandro; et al. (Biology of Sport, 2024)
We aimed to identify how physical activity (PA), within the context of a Mediterranean diet, affects metabolic variables and gut microbiota in older individuals with overweight/obesity and metabolic syndrome. Observational analysis was conducted as part of the PREDIMED Plus study with 152 males and 145 females with overweight/obesity and metabolic syndrome. General assessments, anthropometric and biochemical measurements, and gut microbial 16S rRNA sequencing data were analyzed at baseline and 1-year of follow-up. Participants were stratified by tertiles of 1-year change in total PA-related energy expenditure ranging from -98.77 to 1099.99 METs (min/week). The total PA percentage of change was reduced in tertile 1 (-44.83±24.94), increased in tertile 2 (28.96±23.33) and tertile 3 (273.64±221.42). Beta diversity analysis showed differences in the gut microbiota population within each tertile group. Significant differences were found at phylum, family, and genus levels in the gut microbiota of the three tertile groups at baseline and 1-year timepoint. Tertile 3, the group with the greatest increase in PA, was characterized by increases in their levels of Sutterella, Bilophila , and Lachnospira bacteria as well as a reduction in Collinsella . Moreover, this tertile showed a different pattern in its predicted metabolic capacities to the other groups. Our results have demonstrated that changes in PA such as lifestyle and Mediterranean diet induces specific variations in the gut microbiota profile. This modulation of gut microbiome populations and their metabolic capacities may contribute to the health of the aged individuals with overweight/obesity and metabolic syndrome.